Neutrino Mass Generation from the Perspective of Presymmetry - Matute-Carvajal, E (World Scientific Publishing Co. Pte Ltd, 2019)
The Standard Model (SM) with one right-handed neutrino per generation is revisited with presymmetry being the global U(1)B-L symmetry of an electroweak theory of leptons and quarks with initially postulated symmetric fractional charges. The cancellation of gauge anomalies and the non-perturbative normalization of lepton charges proceed through the mixing of local and topological charges, the global B - L measuring the induced charge associated with a unit of topological charge, and the mathematical replacement of the original fractional charges with the experimentally observed ones. The U(1)B-L symmetry of the SM with Dirac neutrinos is seen as a residual presymmetry. High-scale and low-scale seesaw mechanisms proposed to explain the mass of neutrinos are examined from the perspective of presymmetry, be they of Majorana or pseudo-Dirac type. We find that the tiny mass splitting in pseudo-Dirac neutrinos and the mass of heavy neutrinos ride on the opposite ends of the seesaw. We show that pseudo-Dirac neutrinos contain extra sterile neutrinos with imprints of presymmetry and for heavy ones we get constraints favoring the low-scale linear seesaw over the inverse variant. Â© 2019 World Scientific Publishing Company.